PENETAPAN KADAR NITRAT PADA IKAN KALENG SARDEN SECARA SPEKTROFOTOMETRI VISIBLE - Yettrie Simarmata; Siti Nurbaya; Nina Paramita; Vivi Purwandari (Jurnal Farmanesia, 2019)
Canned fish is a food that is synonymous with preservatives and food coloring. In the manufacturing process, manufacturers often use natural preservatives to lower production costs. This research is descriptive research. The research location is at PT. Mutifa. Aims to determine how much nitrate levels in branded canned sardines are sold at supermarkets in the city of Stabat whether they meet the requirements of SNI or not. From the results of the study, the levels of nitrate with Brand A were 0.00694% and sardines with Brand B were 0.0453% with a maximum wavelength of 435 nm. According to regulations set by the government according to SNI Number 01-35481994 nitrate levels should not be more than 0.2%. From all samples of canned sardines studied, it was found that nitrate levels were low and did not exceed SNI requirements.